The Mirror of Afrofuturism. Issue 1 (March 2020) - Delany, Samuel R.
Abstract : Unless we set up our critical mirrors very carefully, arguably there is no such thing as Afrofuturism. I contend that what is needed for Afrofuturism is black characters in the future, irrespective of the writer's race. I begin with the term's coining by white critic Mark Dery and examine Afrofuturism in Theodore Sturgeon's More Than Human (1953), Alfred Bester's The Stars My Destination (1956), Thomas Disch's Camp Concentration (1968), and Octavia E. Butler's "Amnesty" (2003). I repeat: to the extent Afrofuturism concerns science fiction and not the range of all the arts, including painting and music, classical and jazz, it requires writers writing about black characters in the future. Afrofuturism is pretty much anything you want it to be and not a rigorous category at all.